PENGEMBANGAN MODUL KALKULUS 2 PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA DI STKIP PGRI SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2013)
Students' abilities can be developed through lectures, one of which is variable Calculus 2. In order for the maximum tuition required of a material that can support course lectures. In West Sumatra, Padang PGRI STKIP students only rely on one textbook only when the lectures, so the motivation and low student interest in learning. Therefore it takes a lecture materials that can help facilitate students in the lecture, which is a modul. The purpose of this study is to develop a modul valid, practical and effective in subjects STKIP PGRI Calculus 2 in West Sumatra. This study is a research development. This modul was developed by using the 4D model (define, design, develop, and desseminate). Phase desseminate not done. The data was collected with the validation and testing of the modul. modul is validated by the lecturer and expert Calculus 2, as well as Indonesian lecturers. Tests carried out on mathematics education students STKIP PGRI West Sumatera to know praktikalitas and effectiveness of the modul. The results showed that: 1) modul is valid (including the content and construct validity) of the validator's point of view, 2) the use of modul in the lecture did not experience significant barriers. The book is a practical work according to students and lecturers; and 3) modul have been effective. This is evident from the activities of students and high motivation to learn after the lecture.